Profile of the genomic characteristics and comparative studies of five Trichiuridae species by genome survey sequencing - Song, Na; Zhao, Xiang; Cai, Chuangeng; Gao, Tianxiang (Frontiers in Marine Science, 2022)
Trichiuridae fish are economically important species and widely distributed across the nearshore to open ocean. In the present study the genomic survey sequencing method was used to analyze the genome characters of 5 Trichiuridae fish. The calculated genome size was 913Mb, 868Mb, 871Mb, 747Mb and 670Mb for T. japonicus, T. nanhaiensis, T. brevis, L. savala and E. muticus, respectively. The average GC content for 5 Trichiuridae fish ranged from 39.59% to 42.05%, the repeat sequence content ranged from 33.21% to highest 45.87%. The high heterozygous ratio of E. muticus was highest, and L. savala was smallest. The proportion of microsatellite motifs showed a decreasing trend with the increase of repeat numbers: the dinucleotide repeats were dominant, following by the trinucleotide repeats, tetranucleotide repeats, pentanucleotide repeats and hexanucleotide repeats. The mitochondrial genome of 5 Trichiuridae species was excavated from the genome data and the ML tree revealed that T. japonicus, T. nanhaiensis, T. brevis, L. savala and E. muticus formed into one clade. E. muticus showed earlier expansion than other 4 species and had significant population decline at Last Glacial period by PSMC analysis. This is the first report to sequence and characterize the whole genome of 5 Trichiuridae species.